ANALISIS PERKEMBANGAN AFEKTIF PESERTA DIDIK MELALUI IMPLEMENTASI TOKEN EKONOMI ”STAR ACHIEVEMENT” PADA PEMBELAJARAN IPAS KELAS V SEKOLAH DASAR - Rizkiyah, Maulida Putri; Muhammad Ma'dinul In'am Al; Ummah, Wildatul; Kamil, Muhammad Ma'dinul In'am Al; Mu'alimin; Usriyah, Lailatul (Jurnal Merah Putih Sekolah Dasar, 2026)
This research was motivated by the low learning enthusiasm of fifth-grade students at MI Darul Ulum in Science and Social Studies (IPAS), which only reached 20%. This passive condition hindered students' affective development and cognitive achievement. The purpose of this study was to analyze the effectiveness of the "Star Achievement" token economy strategy as a stimulant for students' affective domain development based on Krathwohl & Bloom's Taxonomy. The study used a descriptive qualitative approach with data triangulation techniques through interviews, questionnaires, and documentation of 20 respondents. The results showed that this strategy was highly effective at the Receiving (90%), Responding (87%), and Valuing (92%) levels. Stars functioned as positive emotional conditioners that increased pride and material retention. However, at the Organization (70%) and Characterization (45%) levels, challenges were found in independent value internalization because students still tended to depend on extrinsic rewards. The conclusion shows that the "Star Achievement" strategy successfully transformed students' mental energy from passive to active and competitive, although the permanent character-building stage requires continuous assistance.